Financial institutions depth and growth in Nepal: Sensitivity to the choice of depth proxy - Keshab Khatri Chettri (Cogent Economics & Finance, 2022)
This paper examines the long-run and short-run growth effects of financial institutions depth in Nepal along with the sensitivity to the choice of proxy representing financial depth. Using annual time-series data for the period from 1980 till 2019, obtained from Quarterly Economic Bulletins published by Nepal Rastra Bank, the study employed autoregressive distribute lag (ARDL) model with bounds testing procedures to examine cointegration. Domestic credit to private sector, broad money supply, total deposits and financial institution's assets are used as proxies for financial institutions depth as indicated by World Bank. Real GDP is used to measure economic growth and the influence of macroeconomic environment is accounted by inflation and trade openness. The bounds tests found cointegration in economic growth functions and the regression results revealed that domestic credit to private sector performed better than other indicators in terms of its significant contribution to economic growth both in the long-run and the short-run. Money supply and financial deposits show significant positive contribution to growth in the long-run. The positive relationship of financial depth indicators with economic growth also supports the supply-leading (finance-led-growth) hypothesis in the long-run. Policies must be aimed at efficient allocation of affordable credit to profitable projects for short-run and long-run growth. Expansionary fiscal and monetary policy and long-term deposits are highly desirable for the long-run growth in Nepal.
Keywords: 330; ARDL; economic growth; financial depth; financial development; Nepal